The Reconstruction of Investment Law based on Social Justice - Batubara, Ismed; Yeltriana, Yeltriana; Saragih, Alkausar (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Investments and aspirations towards social justice are interrelated and influence each other. A well-planned investment begins with legal drafting and a wise effort to potentially become a major force in achieving social justice. For this reason, a thorough approach is needed in designing and implementing investments, taking into account the social and environmental impacts that may arise. This research aims to know the reconstruction of investment law based on social justice as the ideal of social justice is not just a wish, but can be realized through sustainable and comprehensive investments. The research used normative legal research, which is used as the opposite of the empirical/sociological legal research method. The result showed a well-planned investment begins with legal drafting and a wise effort to potentially become a major force in achieving social justice. For this reason, a thorough approach is needed in designing and implementing investments, taking into account the social and environmental impacts that may arise. In this way, the ideal of social justice is not just a wish, but can be realized through sustainable and comprehensive investments.